Creating a Livable Urban Environment: Unseen Problems and Possible Solutions - Horayangkura, Vimolsiddhi (Journal of Architectural/Planning Research and Studies (JARS), 2018)
As Bangkok Metropolitan Area has undergone rapid urbanization, reflecting the influences of Western capitalism under globalization, the liveability of the urban environment has deteriorated. This preliminary research aims to investigate three major dimensions of the urban environment, together with proposals for improvement, as follows: 1) The creation of urban environmental order; 2) The creation of urban symbolism; 3) The creation of urban sustainability. This study also examines the potential increase of professionals qualified to create and rehabilitate livable community environments. Data relating to these three dimensions were collected through physical surveys and a documentation review. In addition, in-depth interviews were conducted to seek supportive and confirmative information. The preliminary research reveals the following findings: Firstly, environmental order can be achieved by solving the problems of sensory overload from advertising, environmental untidiness, discordant architectural styles, and a lack of zoning in entertainment districts. Secondly, regarding urban symbolism, the focus should be on planning urban structures that promote the formation of public image, the conservation of architecture with historical and/or architectonic value, and the creation of iconic architecture in the urban context. Lastly, urban sustainability can be achieved through the provision of more green areas, civic plazas, pedestrian malls, and mixed land use. This analysis of the prevailing decrease in urban livability and the creation of decent urban environments calls for more qualified graduates in urban design, as well as more participatory design processes in which advanced techniques that support community participation, such as gaming simulations, can be employed. Moreover, this research urges for the structuring of a more explicit urban design legal framework that would provide measures to increase urban livability and amenities. In addition, various approaches to enhance professionalism are also discussed. The conclusion of this preliminary research includes a series of research questions to be addressed in future research projects.